2023
DOI: 10.1108/lht-10-2022-0498
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immersive experience, user engagement and perceived authenticity on place satisfaction in the context of augmented reality

Abstract: PurposeThis study aims to measure the effect of augmented reality (AR) on immersive experiences, place satisfaction, user engagement and perceived authenticity.Design/methodology/approachThe population of the research consists of museum visitors visiting the Sakip Sabanci Museum in Turkey, which provides an interactive experience to the audience using AR technology via iPads. The data were collected both online and offline. The research was carried out with 397 questionnaire forms. The hypotheses were tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…These empirical studies provided clear evidence that authenticity not only plays an important role in technological tourism experiences but also is central to understanding heritage tourism. Research has also found authenticity mediated positively between immersive experience and place satisfaction in AR experiences (Dağ et al, 2023). However, these studies lack an explanation as to why authenticity affects tourists' behavioral intentions in a technology‐based tourism experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These empirical studies provided clear evidence that authenticity not only plays an important role in technological tourism experiences but also is central to understanding heritage tourism. Research has also found authenticity mediated positively between immersive experience and place satisfaction in AR experiences (Dağ et al, 2023). However, these studies lack an explanation as to why authenticity affects tourists' behavioral intentions in a technology‐based tourism experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Readers may be interested in recent research on immersive and engagement experiences in AR (Dağ et al , 2023; Dalili Saleh et al , 2021; Li and Liu, 2023), VR and AR experiences in libraries (Greene and Groenendyk, 2021), mobile business simulation games (Chen et al ., 2023), the metaverse (Feng et al , 2022), game animation design (Wu and Tu, 2023; Zhang and Chang, 2023); and game-based learning with AR (Liu et al ., 2023; Yu et al , 2024a, b).…”
Section: Virtual Reality (Vr) Augmented Reality (Ar) and Education Gamesmentioning
confidence: 99%
“…In total, 23 participants evaluated the AR mobile app as 'engaging' rather than 'boring' because of the visual and audio stimuli. With an increased sample size, Da g et al [20] determined the effect of the AR mobile app developed for a museum's visitors. In total, 397 visitors' feedback was analyzed, and it was identified that the immersive experience produced by the AR mobile app had a positive effect on user engagement.…”
Section: Related Work 21 Effects Of Augmented Realitymentioning
confidence: 99%